2010
DOI: 10.1021/la103744x
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Electrocatalytic Properties of Mimochrome VI, a Synthetic Heme Peptide Adsorbed on Gold

Abstract: Mimochrome VI (MC-VI) is a synthetic heme peptide containing a helix-heme-helix sandwich motif designed to reproduce the catalytic activity of heme oxidases. The thermodynamics of Fe(III) to Fe(II) reduction and the kinetics of the electron-transfer process for MC-VI immobilized through hydrophobic interactions on a gold electrode coated with a nonpolar SAM of decane-1-thiol have been determined through cyclic voltammetry. Immobilization slightly affects the reduction potential of MC-VI, which under these cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Mimochrome VI was then immobilized on a self-assembled monolayer (SAM)-coated gold electrode, and its electronic properties were studied with CV. 931 Mimochrome VI showed a quasi-reversible one-electron process. In particular, varying scan rates revealed that there are two conformers of mimochrome VI that possessed a high potential (−106 mV vs NHE) and a low potential (−131 mV vs NHE), respectively, which were hypothesized to correspond to the Δ and Λ conformations of the iron heme cofactor based on an analysis of the Cotton effects of the heme Soret band by CD spectroscopy.…”
Section: De Novo Designmentioning
confidence: 97%
“…Mimochrome VI was then immobilized on a self-assembled monolayer (SAM)-coated gold electrode, and its electronic properties were studied with CV. 931 Mimochrome VI showed a quasi-reversible one-electron process. In particular, varying scan rates revealed that there are two conformers of mimochrome VI that possessed a high potential (−106 mV vs NHE) and a low potential (−131 mV vs NHE), respectively, which were hypothesized to correspond to the Δ and Λ conformations of the iron heme cofactor based on an analysis of the Cotton effects of the heme Soret band by CD spectroscopy.…”
Section: De Novo Designmentioning
confidence: 97%
“…Similar to the previous catalyst, 15.7 mL H 2 was observed after 1.5 h with a TON of 0.35 only. 273 Further exploitation of this artificial enzyme by simple peptide substitution afforded a modified analogue possessing impressive catalytic activity towards oxidation of 2,2 0 -azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS). 26a).…”
Section: Chymotrypsinmentioning
confidence: 99%
“…Goff and co-workers recently followed a similar approach and immobilized a hemin unit onto the MWCNT surface coated with poly-pyrrole-imidazole (Fig. 273. 272 The imidazole unit coordinates to the distal position of the hemin unit leaving the sixth position vacant.…”
Section: Chymotrypsinmentioning
confidence: 99%
“…To tackle this challenge, we developed heme‐protein mimetics (mimochromes) by structure‐based design . Through a miniaturization process, we embedded the metalloporphyrin into a small peptide scaffold and systematically screened the effect of amino‐acid substitutions on function .…”
Section: Figurementioning
confidence: 99%